Protect Bees, Save the Future - Madaleno, I.; Branco, S. (Open Schools Journal for Open Science, 2020)
In this project, students built a hive by adapting remote control systems for its internal environment (temperature and humidity) and external environment (door, fire, location). The solution was aimed at beekeepers, and anyone interested in getting started in the beekeeping industry. The main goals of the project were to facilitate the work of beekeepers and to improve the management, control, and monitoring of hives. The solution created is feasible and satisfies the project’s objectives.